Dual role of allele-specific DNA hypermethylation within the TERT promoter in cancer - Lee, Donghyun D. (2021)
Aberrant activation of telomerase in human cancer is achieved by various alterations within the TERT promoter, including cancer-specific DNA hypermethylation of the TERT hypermethylated oncological region (THOR). However, the impact of allele-specific DNA methylation within the TERT promoter on gene transcription remains incompletely understood. Using allele-specific next-generation sequencing, we screened a large cohort of normal and tumor tissues (n = 652) from 10 cancer types and identified that differential allelic methylation (DAM) of THOR is restricted to cancerous tissue and commonly observed in major cancer types. THOR-DAM was more common in adult cancers, which develop through multiple stages over time, than in childhood brain tumors. Furthermore, THOR-DAM was especially enriched in tumors harboring the activating TERT promoter mutations (TPMs). Functional studies revealed that allele-specific gene expression of TERT requires hypomethylation of the core promoter, both in TPM and TERT WT cancers. However, the expressing allele with hypomethylated core TERT promoter universally exhibits hypermethylation of THOR, while the nonexpressing alleles are either hypermethylated or hypomethylated throughout the promoter. Together, our findings suggest a dual role for allelespecific DNA methylation within the TERT promoter in the regulation of TERT expression in cancer.